Analisis Efikasi Diri (Self – Efficacy) Pada Pembelajaran Matematika Siswa SMA - Citra Mayang Sari; Depriwana Rahmi; Annisah Kurniati; Suci Yuniati (CV. Aksara Global, 2024)
The aim of this research is to discuss the analysis of high school students' self-efficacy in learning mathematics. This research is qualitative research that uses descriptive methods. The instrument used is a non-test instrument, namely a questionnaire. Through the use of a mathematical self-efficacy questionnaire with 30 statements consisting of 10 indicators. The descriptive qualitative research method involved 27 high school students in Kampar. Based on the questionnaire data, it can be concluded that accumulated self-efficacy in mathematics learning is 37.27% in the low category. In percentage terms, it can be described that the indicator of being able to overcome the problems faced is 38.5% in the low category, the indicator of being confident in one's success is 33.17% in the low category, the indicator of having a positive view of the task is 47.74% in the low category , the indicator of being brave enough to face challenges is 42.2% in the low category, the indicator of being brave enough to take risks is 38.55% in the low category, the indicator of being aware of one's strengths and weaknesses is 35.5% in the low category, the indicator of being able to interact with people is 36, 21% in the low category, the indicator of not giving up easily is 40% in the low category, the indicator of having commitment to the tasks given is 28.88% in the low category, the indicator of having great interest in lessons and assignments is 31.96% in the low category.